Probing Receptor Specificity by Sampling the Conformational Space of the Insulin-like Growth Factor II C-domain - Hexnerová, Rozálie; Křížková, Květoslava; Fábry, Milan; Sieglová, Irena; Kedrová, Kateřina; Collinsová, Michaela; Ullrichová, Pavlína; Srb, Pavel; Williams, Christopher; Crump, Matthew P; Tošner, Zdeněk; Jiráček, Jiří; et al. (The Journal of biological chemistry, 2016)
Insulin and insulin-like growth factors I and II are closely related protein hormones. Their distinct evolution has resulted in different yet overlapping biological functions with insulin becoming a key regulator of metabolism, whereas insulin-like growth factors (IGF)-I/II are major growth factors. Insulin and IGFs cross-bind with different affinities to closely related insulin receptor isoforms A and B (IR-A and IR-B) and insulin-like growth factor type I receptor (IGF-1R). Identification of structural determinants in IGFs and insulin that trigger their specific signaling pathways is of increasing importance in designing receptor-specific analogs with potential therapeutic applications. Here, we developed a straightforward protocol for production of recombinant IGF-II and prepared six IGF-II analogs with IGF-I-like mutations. All modified molecules exhibit significantly reduced affinity toward IR-A, particularly the analogs with a Pro-Gln insertion in the C-domain. Moreover, one of the analogs has enhanced binding affinity for IGF-1R due to a synergistic effect of the Pro-Gln insertion and S29N point mutation. Consequently, this analog has almost a 10-fold higher IGF-1R/IR-A binding specificity in comparison with native IGF-II. The established IGF-II purification protocol allowed for cost-effective isotope labeling required for a detailed NMR structural characterization of IGF-II analogs that revealed a link between the altered binding behavior of selected analogs and conformational rearrangement of their C-domains.
Keywords: Antigens, CD; lidé; Receptor, IGF Type 1; Mutation, Missense; receptor IGF typ 1; Amino Acid Substitution; Humans; substituce aminokyselin; Protein Isoforms; Protein Domains; Receptor, Insulin; protein - isoformy; receptor inzulinu; Insulin-Like Growth Factor II; missense mutace; rekombinantní proteiny; Recombinant Proteins; insulinu podobný růstový faktor II; proteinové domény; CD antigeny